Integration of a modified double-infinite Toda lattice by using the inverse spectral problem - Berezansky, Yu.M. (Український математичний журнал, 2008)
The approach to finding the solution of the Cauchy problem for the indicated Toda lattice by means of inverse spectral problem is given.